Functional genomics identifies AMPD2 as a new prognostic marker for undifferentiated pleomorphic sarcoma. Issue 4 (4th December 2018) - Orth, Martin F.; Gerke, Julia S.; Knösel, Thomas; Altendorf‐Hofmann, Annelore; Musa, Julian; Alba‐Rubio, Rebeca; Stein, Stefanie; Hölting, Tilman L. B.; Cidre‐Aranaz, Florencia; Romero‐Pérez, Laura; Dallmayer, Marlene; Baldauf, Michaela C.; et al.
Abstract : Soft‐tissue sarcomas are rare, heterogeneous, and often aggressive mesenchymal cancers. Many of them are associated with poor outcome, partially because biomarkers that can identify high‐risk patients are lacking. Studies on sarcomas are often limited by small sample‐sizes rendering the identification of biomarkers difficult when focusing on individual cohorts. However, the increasing number of publicly available 'omics' data opens inroads to overcome this obstacle. Here, we combine transcriptome analyses, immunohistochemistry, and functional assays to show that high adenosine monophosphate deaminase 2 (AMPD2) is a robust prognostic biomarker for worse outcome in undifferentiated pleomorphic sarcoma (UPS). Gene expression and survival data for UPS from two independent studies were subjected to survival association‐testing. Genes, whose high expression was significantly correlated with worse outcome in both cohorts, were considered as biomarker candidates. The best candidate, AMPD2, was validated in a tissue microarray. Analysis of DNA copy‐number data and matched transcriptomes indicated that high AMPD2 expression is significantly correlated with gains at the AMPD2 locus. Gene set enrichment analyses of AMPD2 co‐expressed genes in both transcriptome datasets suggested that AMPD2 ‐high UPS are enriched in tumorigenic signatures. Consistently, knockdown of AMPD2 by RNA interference in an UPS cell line inhibited proliferation in vitro and tumorigenicity in vivo . Collectively, we provide evidence that AMPD2 may serve as a biomarker for outcome prediction in UPS. Our study exemplifies how the integration of 'omics' data, immunohistochemistry, and functional experiments can identify novel biomarkers even in a rare sarcoma, which may serve as a blueprint for biomarker identification for other rare cancers. Abstract : What's new? Undifferentiated pleomorphic sarcomas (UPS), which are often associated with poor patient outcome, pose significant clinical challenges. An important reason for this is the absence of biomarkers capable of distinguishing patients at high risk of aggressive disease. Here, using bioinformatic and immunohistochemical analyses, the authors probed gene expression datasets for prognostic biomarkers in UPS patients. Patients with poor outcome were found to express intratumorally high levels of adenosine monophosphate deaminase 2 ( AMPD2 ), an enzyme involved in purine metabolism. Analyses revealed correlations between AMPD2 overexpression and copy number variations identified in UPS cohorts. AMPD2 overexpression was further associated with UPS tumor growth.